Studi Pengembangan Kawasan Terbuka Publik Tepian Air pada Kawasan Pusat Pemerintahan Kabupaten Sintang - Ragil Faza Erando; Caesar Destria; Ridho Fajar Abuyahman (Universitas Medan Area, 2026)
Space is a place that includes land space, sea space, air space, which is an area where humans and other living creatures carry out activities and maintain survival (UU No. 26 of 2007 concerning spatial planning). Open spaces are spaces in the city that are wider in the form of areas or elongated areas/lanes and in their use are open without buildings (Dinas Pekerjaan Umum, 2008). Public space itself is an important element that must exist in every city/district, which can be in the form of parks, sports venues, plazas and recreation parks. Sintang Regency is one of the regencies in West Kalimantan. Sintang Regency has great potential in terms of culture, tourism, and also the need for public open space. The people of Sintang Regency certainly need a place or space to carry out various activities ranging from sports, space for recreation or relaxing. One of the public open spaces in Sintang Regency is Bungur Beach Kapuas Sintang Park, which is a public open space area located on the water's edge and in the middle of the government center of Sintang Regency. And purpose of this research was to find solutions to problems related to the need for Waterfront public space in the central government area of ​​Sintang Regency.